1841 Ala. Acts 148 - 49, Of Miscellaneous Offences, ch. 7, § 4 - (:unkn) unknown (General Publisher, 1841)
Prohibited the concealed carrying of “a bowie knife, or knife or instrument of the like kind or description, by whatever name called, dirk or any other deadly weapon, pistol or any species of firearms, or air gun,” unless the person is threatened with an attack or is traveling or “setting out on a journey.” Punished by a fine of $50-100.
Keywords: CARRY